Imported powdered milk versus local production in West Africa: Towards a new industrial model? - (:unkn) unknown (My University, 2012)
Based on two cases from the dairy industry, the first in Senegal and the second in Mali, this study intends to analyse the strategies involved in crude milk collection in West Africa, even though the market is dominated by powdered milk. In fact, when their commercial and supply strategies are considered, with a Fulani dairy and a milk powder industrial user, these two approaches do not appear as different as it at first might seem. The future of the dairy industry is undoubtedly a mixed model relying on both powdered and fresh milk for a segmented market. Although a full milk industrial sector still appears impossible, local milk seems well to be integrated into the West African circuit.
Keywords: African Research